Executive Committee Minutes 2014-01-16 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 1/16/14 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Art Studio BA and BFA revision approved for the Senate consent calendar. Request for Reassigned time for 2014 – 2015 approved. Revision to the Course Outline Policy approved for the Senate agenda. Vice President of Administration and Finance Report. Proposed student fee to support graduation discussion. Schedule 25 Fall 2014 pilot review referred to EPC and FSAC. Chief Student Affairs Officer Report. EPC Report. FSAC Report. SAC Report. Associated Students Report. Senate agenda approved.